1978
DOI: 10.1136/hrt.40.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Do patients take digoxin?

Abstract: Plasma digoxin concentrations on admission to hospital have been compared with levels on day 8 in a group of 50 patients who were maintained on their preadmission digoxin doses for 7 days. In the absence of a change in renal function, 18 patients (36%) had higher levels on day 8 and were considered to be non-compliant: a further 7 patients (14%) had lower levels on day 8 suggesting that before admission they had been taking more than their prescribed digoxin dose. Fifty per cent were, therefore, taking their d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1978
1978
1994
1994

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…In a recent study of sixty patients being admitted to hospital in emergency (Johnston, Kelly & McDevitt, 1978) in which plasma digoxin concentrations on admission were compared with levels obtained after seven days treatment with their pre-admission digoxin doses, it was found that almost one-half of the patients were taking their digoxin improperly-nearly onethird of the total group were considered to be taking too little digoxin and to be non-compliant.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study of sixty patients being admitted to hospital in emergency (Johnston, Kelly & McDevitt, 1978) in which plasma digoxin concentrations on admission were compared with levels obtained after seven days treatment with their pre-admission digoxin doses, it was found that almost one-half of the patients were taking their digoxin improperly-nearly onethird of the total group were considered to be taking too little digoxin and to be non-compliant.…”
Section: Introductionmentioning
confidence: 99%
“…The limits are larger than those previously selected, both in relation to plasma digoxin and serum creatinine (Johnston et al, 1977). Reanalysis of compliance in the original admission study (Johnston et al, 1977) using these new limits shows that of the 50 patients studied 17 (34%), instead of 18 previously, would be adjudged to have been taking less and 5 (10%), instead of 7 previously, more than the prescribed daily digoxin dose before admission to hospital.…”
Section: Variations Of Plasma Digoxin Concentrations In the Equilibrimentioning
confidence: 80%
“…Reanalysis of compliance in the original admission study (Johnston et al, 1977) using these new limits shows that of the 50 patients studied 17 (34%), instead of 18 previously, would be adjudged to have been taking less and 5 (10%), instead of 7 previously, more than the prescribed daily digoxin dose before admission to hospital. Overall these new standards would mean 44 (rather than 50) per cent were taking their digoxin improperly.…”
Section: Variations Of Plasma Digoxin Concentrations In the Equilibrimentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, improved compliance may not always be beneficial-we have shown previously that in some non-compliant patients, given their prescribed daily digoxin dosage in hospital, plasma digoxin concentrations rose into the potentally toxic range (Johnston, Kelly & McDevitt, 1978). Reduced frequency of daily dosage administration may not affect compliance greatly.…”
Section: Discussionmentioning
confidence: 94%